Sinapine Thiocyanate Ameliorates Vascular Endothelial Dysfunction in Hypertension by Inhibiting Activation of the NLRP3 Inflammasome - Liu, Yang; Yin, Hong-lin; Li, Chao; Jiang, Feng; Zhang, Shi-jun; Zhang, Xin-rong; Li, Yun-lun (Frontiers in Pharmacology, 2021)
The increase of blood pressure is accompanied by the changes in the morphology and function of vascular endothelial cells. Vascular endothelial injury and hypertension actually interact as both cause and effect. A large number of studies have proved that inflammation plays a significant role in the occurrence and development of hypertension, but the potential mechanism between inflammation and hypertensive endothelial injury is still ambiguous. The purpose of this study was to explore the association between the activation of NLRP3 inflammasome and hypertensive endothelial damage, and to demonstrate the protective effect of sinapine thiocyanate (ST) on endothelium in hypertension. The expression of NLRP3 gene was silenced by tail vein injection of adeno-associated virus (AAVs) in spontaneously hypertensive rats (SHRs), indicating that activation of NLRP3 inflammasome accelerated hypertensive endothelial injury. ST not only protected vascular endothelial function in SHRs by inhibiting the activation of NLRP3 inflammasome and the expression of related inflammatory mediators, but also improved AngII-induced HUVEC injury. In summary, our results show that alleviative NLRP3 inflammasome activation attenuates hypertensive endothelial damage and ST ameliorates vascular endothelial dysfunction in hypertension via inhibiting activation of the NLRP3 inflammasome.